Toeplitz Operators Defined between Köthe Spaces - Doğan, Nazlı (Cornell University, 2024)
The aim of this paper is to define Toeplitz operators between Köthe spaces, especially power series spaces. We determine the conditions for continuity and compactness of these operators. We define the concept of S-tameness of a family of continuous operators. We construct some conditions on S-tameness for the families consisting of Toeplitz operators.
Keywords: Toeplitz Matrix; Köthe Spaces; Compact Operators